“Na Real presença de Vossa Majestade": as petições ultramarinas e a governação colonial (século XVIII) - Fernandes, Renata Silva (2023)
This article intends to examine the petitionary mechanism as a particular modality of political communication between the Portuguese overseas vassals and the monarch, from his Overseas Council. My goal is to scrutinize the various uses of petitions and their framing in the governmental logic of colonization as a broad, multifaceted, and dynamic institutional channel of relationship between subjects and the royal power based in Lisbon. Considering the analytical potential of the reconstitution of the petition–form of processing–response circuit, part of the corpus housed in the Overseas Historical Archive, I propose to compare both the petitionary documents themselves, in the form of the Single Documents, and the decision-making circuits embodied in the registry books of the institution (Codices). At first, I make a discursive-formal analysis of the petitions. Then, I discuss the legal-institutional dynamics of treatment and response to the parties’ petitions, based on the Overseas Council’s Provisions Record Books. The main hypothesis defended is that the petitions and their procedures and responses point to governance practices, submission models and forms of control not always made explicit by historiography or seen as merely protocol. They are, however, very important sources of the institutional practices of the organizational complex of the Portuguese region in its relations with colonial societies.